Bioethics between Religion and Philosophy - Abdul-Ameer, Asst.Prof.Dr. Ehsan Ali (Al-Adab Journal, 2020)
The research deals with the subject of “Bioethics”, Which means the ethics of the biomedical field, It represents an arena for science to meet with ethics, It includes a group of various disciplines such as, physicians, biologists, clergy, philosophers, law men, politics and economics, psychologists and sociologists, To establish standards and controls for medical practices in the field of biology, Through this topic, we will try to detect a set of ethical problems resulting from technological development in the field of medicine and biology, For example: Sexual transformation, artificial insemination, abortion, organ transplantation, euthanasia and human cloning, With the presentation of visions related to it by clerics and philosophers, Our vision is holistic on those topics that emerged from the great scientific development in the field of medicine and biology.